CO2 mineralization maintenance coast engineering ecological building material building block and preparation method thereof

By combining industrial solid waste with CO2 to prepare CO2 mineralized coastal engineering eco-building blocks, the problems of resource waste and greenhouse gas emissions are solved, providing high-performance coastal engineering eco-building materials and realizing CO2 fixation and resource utilization.

CN120841893APending Publication Date: 2025-10-28ZHEJIANG GUOHUA ZHENENG POWER GENERATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511051141.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing technologies fail to effectively utilize industrial solid waste and CO2, leading to resource waste and greenhouse gas emissions, and there is a lack of environmentally friendly building materials with excellent performance in the marine engineering construction field.

Method used

By combining industrial solid wastes such as bottom ash, fly ash, steel slag, and cement with CO2, ecological building material blocks for coastal engineering with CO2 mineralization and maintenance are prepared. The alkali metal components react to form calcium carbonate crystals, which enhances the material properties, and CO2 mineralization and maintenance are carried out to fix carbon dioxide.

Benefits of technology

It has achieved CO2 fixation and resource utilization of industrial waste, provided ecological building materials for coastal engineering with excellent physical properties, reduced production costs, and enhanced market competitiveness and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841893A_ABST
    Figure CN120841893A_ABST
Patent Text Reader

Abstract

The invention discloses a CO2 mineralization maintenance coast engineering ecological building material building block and a preparation method thereof. The CO2 mineralization maintenance coast engineering ecological building material building block comprises 10-20 parts of furnace bottom slag, 10-20 parts of fly ash, 0-5 parts of gypsum, 10-15 parts of steel slag, 10-20 parts of cement, 25-35 parts of sand and 5-15 parts of granite. The novel coast engineering ecological building material which has excellent carbon sequestration capability and excellent physical properties is successfully developed by using the industrial waste residues as the main raw materials in a large scale and performing synergistic effect with the carbon dioxide, so that resource utilization of industrial byproducts is promoted, and the cost is reduced. And moreover, energy conservation and emission reduction in the production process are realized through the process, and meanwhile, the overall production cost is effectively reduced by reducing the emission of greenhouse gases, so that the market competitiveness and environmental benefits of the maritime work building material building blocks are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an ecological building material block for CO2 mineralization conservation of coastal engineering and its preparation method. Background Art

[0002] Carbon dioxide (CO2) is a key factor contributing to global warming, with its most significant environmental impact being the exacerbation of the greenhouse effect. The greenhouse effect refers to the phenomenon where gases in the Earth's atmosphere trap solar radiation, leading to a rise in global average temperature. This effect can cause polar ice caps to melt, sea levels to rise, and consequently threaten the safety of coastal cities. Furthermore, climate warming can trigger a series of ecological and social problems, including land degradation and declining agricultural productivity. Therefore, the urgency of reducing carbon dioxide emissions to mitigate climate change is increasingly evident.

[0003] my country's industrial solid waste is increasing year by year. Currently, coal-fired power plants remain the mainstay of China's energy industry, generating large amounts of solid waste such as fly ash and desulfurization gypsum annually, while also emitting large amounts of CO2. This not only puts enormous pressure on the surrounding environment but also wastes resources. In recent years, the concept of low-carbon green building materials has been proposed and continuously developed and improved, aiming to reduce the carbon footprint of building material production cycles through technologies such as "solid waste resource utilization," "CO2 resource utilization," and "low-carbon cement," in order to achieve a negative carbon effect. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies, this invention provides an eco-friendly building material block for CO2 mineralization and conservation of coastal engineering and its preparation method. By innovatively combining industrial solid waste and CO2, it effectively promotes CO2 fixation and also has excellent physical properties, providing an environmentally friendly and high-performance solution for the marine engineering construction industry.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: an ecological building material block for CO2 mineralization and conservation of coastal engineering, comprising: 10-20 parts of bottom slag, 10-20 parts of fly ash, 0-5 parts of gypsum, 10-15 parts of steel slag, 10-20 parts of cement, 25-35 parts of sand, and 5-15 parts of gravel.

[0006] As a preferred embodiment of the present invention, the particle size of the bottom slag is 0.12-5.15 mm.

[0007] As a preferred embodiment of the present invention, the fly ash particle size is 0-0.15 mm.

[0008] As a preferred embodiment of the present invention, the steel slag particle size is 0.15-5.45 mm.

[0009] A method for preparing an ecological building material block for CO2 mineralization and coastal conservation engineering includes the following steps: S1. Mix the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel evenly according to the mass ratio, add water and stir to obtain the mixture; Weigh out equal amounts of the mixture and inject them into the mold in several batches. After the injection process is completely finished, place the mold containing the mixture on a vibrating table and vibrate it. S3: Place the mold filled with the mixture on the table of the tablet press, then start the pressurization program to the preset molding pressure value, and maintain this pressure for a period of time to ensure that the mixture is uniform and dense in the mold; S4: Remove the specimen from the mold and place it in the curing chamber for preliminary pre-curing. After the pre-curing is completed, transfer the specimen to the mineralization curing kettle for CO2 mineralization curing. S5: After completing the CO2 mineralization curing process, the gas in the curing vessel is discharged, and then the sample is placed at room temperature to continue curing in the natural environment.

[0010] In step S1, the amount of water added to the solid raw material is 10-15% of its mass, for example, 12%; the stirring operation is carried out at a speed of 180-240 r / min, for example, 220 r / min, and the duration is controlled at 5-8 min.

[0011] Step S2 involves shaking the mixture on a shaking table to remove air bubbles, with the shaking time set to 30-60 s.

[0012] In step S3, the preset molding pressure value is 10-15 MPa, for example 12 MPa, and this pressure is maintained for 10-60 s to ensure that the material is fully molded.

[0013] In the pre-curing stage of step S4, the specimens are placed in a curing chamber where the temperature is maintained at 20-25 degrees Celsius (e.g., 22 degrees Celsius) and the humidity is controlled at 65-75% RH (e.g., 70% RH). The pre-curing time is 8-48 hours, e.g., 12-36 hours, depending on the needs. Finally, in the CO2 mineralization curing stage of step S4, the specimens undergo mineralization curing at room temperature, with the CO2 pressure maintained at 0.8-1.2 MPa, and the mineralization curing time set to 2-8 hours to promote the carbonation reaction of the material. Compared with existing technologies, the beneficial effects of this invention are as follows: By reacting carbon dioxide with alkali metal components such as calcium and magnesium in industrial solid waste, including bottom slag, steel slag, cement, and fly ash, the formation of calcium carbonate crystals and amorphous calcium-modified silica gel is promoted. These products fill pores and enhance polymerization within the brick body, while also achieving effective absorption of large amounts of carbon dioxide. This invention is composed of cement, slag, bottom slag, and silicates mixed in a specific ratio. Compared with conventional cement, it exhibits superior mechanical properties and durability. Especially in harsh marine environments, it also possesses excellent resistance to water erosion and radiation, enabling it to withstand long-term marine environmental impacts. Simultaneously, by utilizing industrial waste as the main raw material on a large scale and synergistically combining it with carbon dioxide, this invention successfully develops a new type of coastal engineering ecological building material that possesses both excellent carbon sequestration capabilities and superior physical properties. This not only promotes the resource utilization of industrial by-products but also achieves energy conservation and emission reduction in the production process. Furthermore, by reducing greenhouse gas emissions, it effectively lowers overall production costs, thereby enhancing the market competitiveness and environmental benefits of marine engineering building blocks. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of the first process of the present invention; Figure 2 This is a schematic diagram of the second process of the present invention. Detailed Implementation

[0015] To make the technical means, creative features, and achieved objectives and effects of this invention easier to understand, the invention is further described below with reference to specific embodiments. However, the following embodiments are merely preferred embodiments of this invention and not all of them. Other embodiments obtained by those skilled in the art based on the embodiments described herein without creative effort are all within the protection scope of this invention. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods, and the materials and reagents used in the following embodiments are commercially available unless otherwise specified.

[0016] The raw materials used in each embodiment are as follows: Bottom ash is a byproduct discharged from the bottom ash discharge port after being burned as fuel in the boiler furnace. It is mainly composed of chemical components such as SiO2, CaO, Al2O3, Fe2O3, and MgO. The particle size of bottom ash is 0.12-5.15 mm.

[0017] Fly ash, a fine powder byproduct captured from flue gas produced during coal combustion, mainly contains oxides such as SiO2, Al2O3, FeO, Fe2O3, CaO, and TiO2. In this invention, the fly ash has an average particle size range of 0-0.15 mm.

[0018] Steel slag is an industrial byproduct formed during the smelting of pig iron due to the oxidation of impurity elements such as silicon, manganese, phosphorus, and sulfur, as well as the combination of salts formed by the reaction of these oxides with the solvent. It is mainly composed of chemical components such as SiO2, CaO, Al2O3, Fe2O3, and MgO, and has an average particle size range of 0.15-5.45 mm.

[0019] Example 1: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0020] The marine engineering block of this embodiment has a compressive strength of 27.9 MPa and a carbon fixation content of 5.9%.

[0021] Example 2: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 24 hours for pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0022] The marine engineering block of this embodiment has a compressive strength of 26.1 MPa and a carbon fixation content of 5.3%.

[0023] Example 3: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 14% of its mass. The stirring operation is carried out at a speed of 200 r / min and the duration is controlled within 5 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0024] The marine engineering block of this embodiment has a compressive strength of 24.3 MPa and a carbon fixation content of 5.1%.

[0025] Example 4: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 30 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 14 MPa, and hold the pressure for 40 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0026] The marine engineering block of this embodiment has a compressive strength of 26.6 MPa and a carbon fixation content of 5.5%.

[0027] Example 5: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 10 parts bottom ash, 20 parts fly ash, 5 parts gypsum, 10 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0028] The marine engineering block of this embodiment has a compressive strength of 23.8 MPa and a carbon fixation content of 5.0%.

[0029] Example 6: The CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment comprise the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization and conservation coastal engineering ecological building material blocks of this embodiment includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.2 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0030] The marine engineering block of this embodiment has a compressive strength of 28.2 MPa and a carbon fixation content of 6.1%.

[0031] Compare with Example 1: The difference between this comparative example and Example 1 is that no CO2 gas source was introduced.

[0032] The CO2 mineralization conservation coastal engineering ecological building material block of this comparative example comprises the following raw materials in parts by weight: 15 parts bottom ash, 15 parts fly ash, 3 parts gypsum, 12 parts steel slag, 15 parts cement, 30 parts sand, and 10 parts gravel. The preparation method of the CO2 mineralization conservation coastal engineering ecological building material block of this comparative example includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and 70% RH for 12 hours for pre-curing. Step 5: After the pre-curing is completed, place it at room temperature for natural curing (temperature 22 °C, humidity 70% RH) for 7 days to obtain marine engineering building material blocks.

[0033] The test results showed that the compressive strength of the marine engineering block in this control example was 20.7 MPa, and the carbon fixation content was 0%.

[0034] Compare with Example 2: The difference between this comparative example and Example 1 is that no cement was added. The CO2 mineralization conservation coastal engineering ecological building material blocks of this comparative example comprise the following raw materials in parts by weight: 20 parts bottom ash, 20 parts fly ash, 3 parts gypsum, 12 parts steel slag, 30 parts sand, and 15 parts gravel. The preparation method of the CO2 mineralization conservation coastal engineering ecological building material blocks of this comparative example includes the following steps: Step 1: Weigh the bottom ash, fly ash, gypsum, steel slag, sand and gravel according to the proportion, mix them evenly, then add water and stir to obtain a mixture. The amount of water added to the solid raw materials is 12% of its mass. The stirring operation is carried out at a speed of 220 r / min and the duration is controlled within 6 min. Step 2: Weigh out the same mass of the mixture and inject it into the mold in three batches. After each batch of the mixture is injected into the mold, ensure that the mixture in each part of the mold is evenly distributed by full and uniform vibration. Then, after the injection process is completely finished, place the mold containing the mixture on the vibration table and vibrate for 40 seconds. Step 3: Place the mold filled with the mixture precisely on the table of the tablet press, then start the pressurization program to the preset molding pressure value of 12 MPa and hold the pressure for 30 seconds; Step 4: Remove the specimen from the mold and place it in a curing chamber with controlled environmental conditions of 22 °C and humidity of 70% RH for 12 hours of pre-curing. After pre-curing, transfer the specimen to a dedicated mineralization curing vessel, maintain the CO2 pressure at 1.0 MPa, and set the mineralization curing time to 4 hours for CO2 mineralization curing. Step 5: After the mineralization curing is completed, remove the sample after the air is released and place it in room temperature for natural curing (temperature is 22 °C, humidity is 70% RH) for 7 days to obtain marine engineering building material blocks.

[0035] The test results showed that the compressive strength of the marine engineering block in this control example was 18.6 MPa and the carbon fixation content was 4.2%.

[0036] In summary, the preparation method of the CO2 mineralization and conservation coastal engineering ecological building material block provided by the present invention can be used for marine engineering blocks. This marine engineering block can not only effectively absorb CO2 and reduce greenhouse gas emissions, but also utilize solid waste such as industrial waste residue to achieve resource recycling. At the same time, due to its simplified production process and low-cost material use, this block has extremely high economic competitiveness.

[0037] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can include direct contact between the first and second features, or contact between the first and second features through another feature between them. Furthermore, "above," "over," and "on top" of the second feature includes the first feature directly above or diagonally above the second feature, or simply indicates that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature includes the first feature directly below or diagonally below the second feature, or simply indicates that the first feature is at a lower horizontal level than the second feature.

[0038] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the foregoing embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. An ecological building material block for CO2 mineralization conservation coastal engineering, characterized in that: include: 10-20 parts bottom ash, 10-20 parts fly ash, 0-5 parts gypsum, 10-15 parts steel slag, 10-20 parts cement, 25-35 parts sand, and 5-15 parts gravel.

2. The ecological building material block for CO2 mineralization conservation coastal engineering according to claim 1, characterized in that: The particle size of the bottom slag is 0.12-5.15 mm.

3. The ecological building material block for CO2 mineralization conservation coastal engineering according to claim 2, characterized in that: The particle size of fly ash is 0-0.15 mm.

4. The ecological building material block for CO2 mineralization conservation coastal engineering according to claim 3, characterized in that: The particle size of steel slag is 0.15-5.45mm.

5. A method for preparing an ecological building material block for CO2 mineralization conservation coastal engineering according to any one of claims 1-4, characterized in that: S1: Mix the bottom ash, fly ash, gypsum, steel slag, cement, sand and gravel evenly according to the mass ratio, add water and stir to obtain the mixture; S2: Weigh out equal amounts of the mixture and inject them into the mold in batches. After the injection process is completely finished, place the mold containing the mixture on a vibrating table and vibrate it. S3: Place the mold filled with the mixture on the table of the tablet press, then start the pressurization program to the preset molding pressure value, and maintain this pressure for a period of time to ensure that the mixture is uniform and dense in the mold; S4: Remove the specimen from the mold and place it in the curing chamber for preliminary pre-curing. After the pre-curing is completed, transfer the specimen to the mineralization curing kettle for CO2 mineralization curing. S5: After completing the CO2 mineralization curing process, the gas in the curing vessel is discharged, and then the sample is placed at room temperature to continue curing in the natural environment.